Solid waste-derived carbon nanomaterials for supercapacitor applications: a recent overview. Issue 5 (5th February 2021) - Tatrari, Gaurav; Karakoti, Manoj; Tewari, Chetna; Pandey, Sandeep; Bohra, Bhashkar Singh; Dandapat, Anirban; Sahoo, Nanda Gopal
Abstract : Universal solid waste management and its hazardous effects on the ecology, ecosystem, and the global human health index are some of the major issues that are currently threatening our future. Abstract : Universal solid waste management and its hazardous effects on the ecology, ecosystem, and the global human health index are some of the major issues that are currently threatening our future. The overproduction of solid waste materials is mainly the consequence of human population explosion and extraordinary increase in global economy along with global productivity. Due to the rapid growth in global population and the related demands, the production of solid waste materials is increasing day by day. In order to have a better solution to solid waste management, the best ethical way is to convert solid waste materials into valuable carbon-based nanomaterials (CNMs) such as CNT, graphene, and carbon quantum dots (CQDs), which can further work as precursors in energy storage devices. This critical review summarizes the recent progress in the structural forms and current situational analysis of universal solid waste based CNMs. It also includes broadly discussed issues, starting with the current waste situation analysis of global energy crisis and the production of graphene, including its counterparts, as the precursors for supercapacitor applications. A paradigm study of various solid waste derived CNMs with their significance, which, in particular, depends upon the types of CNMs and the classification of solid waste derived CNMs on the basis of different types of pore size and pore distribution, has been carried out. The various structural modifications and their effects on the electrochemical properties have been discussed thoroughly for supercapacitor applications including their future possibilities and scope. The review outlines the crucial mechanism followed during the charge storage of different kinds of supercapacitors and various electrochemical calculations involved during the performance testing of the fabricated device. We hope that the target audience, belonging to the energy or material science field, may acquire relevant information from this review, which may further help them to design futuristic studies in the field.